Establishing Minimal Clinically Important Differences for the Quality of Life Instrument in Patients With Breast Cancer QLICP-BR (V2.0) Based on Anchor-Based and Distribution-Based Methods - Li, Fei; Liu, Yuxi; Wan, Chonghua; Zhou, Jiali; Tan, Jianfeng; Chen, Huanwei (Frontiers in Oncology, 2022)
Abstract Objective: To determine the minimal clinically important differences (MCIDs) for the Quality of Life Instruments system in breast cancer patients, QLICP-BR (V2.0), which consist of the general module of 32 items classifying into 4 domains and the specific module of 10 items. Methods: According to the scoring rule of QLICP-BR (V2.0), the scores of each domain and the overall of the scale were calculated. The MCIDs of this scale were established by anchor-based and distribution-based methods. The anchor method used the Q29 item in the EORTC QLQ-C30 scale as anchors and defined the treatment effectiveness of the anchor-based method using criteria A (one level improvement after treatment) and B (at least one level improvement after treatment), while methods of effect size (ES), standard error of measurement (SEM), and reliability change index (RCI) were used in distribution-based methods. Results: Using the anchor method, according to standard A, the MCIDs of the physical domain (PHD), psychological domain (PSD), social domain (SOD), common symptoms and side effect domain (SSD), core/general module (CGD), specific domain (SPD), and total (TOT) were 16.24, 11.37, 11.31, 12.07, 11.49, 10.69, and 11.23 respectively; according to standard B, the MCIDs of PHD, PSD, SOD, SSD, CGD, SPD, and TOT were 18.88, 15.14, 14.10, 14.50, 13.93, 12.17, and 14.23 respectively. In the distribution-based MCID study, when ES = 0.8, the MCID values of each domain and the total score of the scale were 9.14, 10.34, 8.34, 10.54, 6.79, 9.73, and 6.96 respectively. The MCIDs calculated when a SEM of 1.96 was used as the intermediary index were 8.38, 11.04, 8.67, 10.00, 7.44, 9.83, and 7.81. The MCIDs calculated when a RCI of 1.96 was used as the intermediary index were 11.84, 15.61, 12.27, 14.14, 10.52, 13.90, and 11.05. Additionally, the MCID value calculated by the two standards of the anchor method was similar to 0.8 ES, 1.96 SEM, and 1.96 RCI. Conclusion: Using the anchor method, 0.8ES, 1.96SEM, and 1.96RCI have a better effect on the minimum clinical important difference of breast cancer and were recommended to be the preferred methods for establishing MCID.